PENGARUH KEGIATAN TEKTONIK DAN GUNUNG API TERHADAP KARAKTERISTIK SEDIMENTOLOGI SEDIMEN NEOGEN AWAL DAERAH BAGIAN TENGAH CEKUNGAN SERAYU - Syaiful Bachri (Pusat Survei Geologi, 2010)
The Early Neogene sediments in the central part of the Serayu Basin have different sedimentological characteristics of one unit from the others. They comprise the mean value of four variables, i.e. (1) sand/shale ratio, (2) bed frequency, (3) smectite / kaolinite ratio or Sm/(Sm+Ko), and (4) quartz/feldspar ratio or K/(K+F). The difference of the mean value of those four variables represents implication of different intensities of tectonic and volcanism activities. The variable values suggest that there was increasing tectonic activity followed by increasing volcanic activity from older rock unit to younger unit.Keywords: sedimentological characteristics, tectonic activity, volcanic activity, Serayu Basin